RISCO DE INFARTO AGUDO DO MIOCARDIO EM PRATICANTES DE MUSCULAÇÃO DE UMA ACADEMIA DA CIDADE DE ITATIAIA-RJ - Thaís de Souza Rosa; Marilene de Oliveira Leite (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
This study aims to evaluate the risk of cardiovascular events in bodybuilders. Were diagnosed in the nutritional status of the study participants and applied the Framingham score to check the risk of myocardial infarction, angina or sudden death in the next 10 years. According to the nutritional diagnosis results were satisfactory, since 95% of the participants interviewed had normal weight, having low risk of developing cardiovascular disease. In relation to the score results were also satisfactory, as based on the results produced by this study, one can conclude that the majority of those treated have lower risk of developing cardiovascular diseases over the next ten years. However Regarding the participants interviewed were observed some of the major risk factors, such as family history, physical inactivity and overweight, which in a small percentage, blood pressure levels presented consistent with hypertension. Porting was concluded that the use of the Framingham score should be encouraged in the context of primary care, as recommended by the guidelines of the SUS, since the possibility of estimating the absolute risk in ten years enables preventive actions, which is also still a need for greater awareness of society in general about life habits, in order to prevent the development of risk factors of cardiovascular diseases.